E-Modul IPS Bermuatan Cerita Rakyat Bali pada Siswa Kelas VI Sekolah Dasar - Ni Wayan Meisya Swandewi; I Gusti Agung Ayu Wulandari; Gusti Ngurah Sastra Agustika (Journal on Education, 2024)
Low student learning outcomes in learning are a problem that occurs in education. The lack of available teaching materials is one of the things that causes these problems. The problem faced by grade VI A and VI B students at SD Negeri 18 Pemecutan is the low learning outcomes of students in science learning caused by the lack of teaching materials in science learning and only relying on teaching materials searched on the internet by teachers. This study aims to (1) describe the process of developing social studies e-module media containing Balinese Folklore Based on Pancasila Student Profile, (2) explain the quality of social studies e-module containing Balinese Folklore Based on Pancasila Student Profile, and (3) find out the effectiveness of social studies containing Balinese Folklore Based on Pancasila Student Profile. The development model used was Dick and Carey. The data collection methods used are observation, interviews, questionnaires, and tests. The subjects of this study were 60 students of grades VI A and VI B SD Negeri 18 Dismissal for the Academic Year 2023/2024. The data analysis techniques used are qualitative descriptive, quantitative descriptive analysis, and inferential statistical analysis. The results of the research conducted were (1) The process of developing social studies e-modules containing Balinese Folklore Based on Pancasila Student Profiles, (2) E-modules were declared valid with expert assessments of subject content with a presentation of 96% of very good categories, instructional design experts with a percentage of 100% of very good categories, learning media experts with a percentage of 94% of very good categories, linguists with a percentage of 98% in the very good category, individual trials with a percentage of 94.16%, and small group trials with a percentage of 89.16% in the good category, (3) the use of e-modules is declared effective as evidenced by the improvement of the teaching results of class students who are taught with social studies e-modules containing Balinese Folklore compared to classes taught with conventional modules.